Step-by-step explanation:
On the left: possible outcome has the value of 1 (1) =
On the right: 1 possible outcome has the value of 1 (1)=
=> the probability of possible P(sum)= 2
= *
=
On the left: possible outcome has the value of 1 =
On the right: 1 possible outcome has the value of 2 =
On the left: possible outcome has the value of 2 =
On the right: 1 possible outcome has the value of 1 =
=> the probability of possible P(sum)= 3
= * + *
=
On the left: possible outcome has the value of 1 =
On the right: 1 possible outcome has the value of 3 =
On the left: possible outcome has the value of 2 =
On the right: 1 possible outcome has the value of 2=
=> the probability of possible P(sum)= 4
= * + *
=
On the left: possible outcome has the value of 2 =
On the right: 1 possible outcome has the value of 3 =
=> the probability of possible P(sum)= 5
= *
=